Jamal aur tota: husnain readers bilingual english & urdu stories (Husnain publishers Lahore, 2019)
Jamal was a curious boy who loved animals. One day, he saw a beautiful parrot in a cage at the market. Its colorful feathers and playful antics captivated Jamal's heart. He begged his parents to buy the parrot, and they finally agreed.